Análise de influência de fatores socioeconômicos no valor adicionado bruto da construção civil - ALEIXO, Anthony Felipe Nery Paiva (2024)
The construction industry is recognized as one of the main driving forces of economic growth and development in a country. Its operations encompass a wide range of activities, from the construction of residential and commercial buildings to road infrastructure, bridges, educational institutions, and health facilities. This sector stands out for its intersectoral interconnections, exerting influence and reflecting on various economic and social aspects. For example, the construction industry is a significant source of direct and indirect employment, requiring a variety of raw materials such as cement, steel, and wood. Additionally, it maintains direct links with the real estate market, the financial system, and urban development. Thus, the economic impact of the construction industry is noteworthy, as investments in this sector not only stimulate immediate economic activity but also generate long-term effects, potentially improving quality of life, expanding access to housing, and contributing to infrastructure development. However, like any economic sector, it is susceptible to economic fluctuations, government regulations, variations in material and labor costs, and is sensitive to social factors such as housing demand, public policies, and changes in consumption patterns. In this context, this study aims to deepen the understanding of one of the main macroeconomic indicators of the Brazilian construction industry, the Gross Value Added (GVA), from the perspective of socio-economic variables. The Ordinary Least Squares technique was employed to explore trends. This investigation will provide a more comprehensive view of how these elements influence and are influenced. As a result, it was possible to consistently infer that the socio-economic variables used have a considerable impact on the Gross Value Added (GVA) of the construction industry. In addition, the statistical relevance of the models that included time and state fixed effects was analyzed and discussed. This paves the way for discussions on the interconnection between socio-economic variables and construction Value Added in Brazil, providing a basis for future research.